The effect of high-intensity interval training (HIIT) on the special endurance and some offensive skills of handball players - Judeh , Younis; hassan, mustafa (Journal of Physical Education, 2025)
The importance of the research emerged in using a type of modern methods as an attempt to improve performance and develop special endurance. A set of exercises in the HIIT style was developed as a comprehensive and intensive training program in a scientifically studied manner that can enhance and develop special endurance and various offensive skills for female handball players. These qualities contribute greatly to increasing endurance and improving their offensive performance on the field. The research aimed to prepare exercises according to the high-intensity interval training (HIIT) method in developing special endurance and offensive skills for female handball players. The researchers adopted the experimental research method by designing a single group with tight control in the pre- and post-tests. The research community was represented by the players of the Al-Talaba Sports Club، numbering (10) players who continue training. They were chosen intentionally. The training program was implemented on Sunday (10/3/2024) until (10/6/2024). The duration of the training program was (12) weeks، with three training units per week، and the total number of training units was (36) training units. The training days were Saturday، Monday and Wednesday. The training unit time (120) minutes، and the time of the main part of the training unit was (80) minutes، and the intensity used ranged from (85 - 95%)، from the first training unit to the last training unit، and the total repetitions ranged from (3-10) and the groups (3-4) within the training unit، and these exercises are characterized by the presence of an intermediate rest between the exercises in the form of positive rest (jogging or stretching exercises)، and the pre-tests were conducted on the research sample on (Saturday and Sunday) corresponding to (10-9/3/2024) at 3 pm، and the experiment was completed by applying the post-tests on Wednesday and Thursday (12-13\6\2024)، and the researchers used the statistical package SPSS version (26) to calculate the values ​​of the arithmetic mean، standard deviation، skewness coefficient، percentage and t-test، and the researchers concluded that the interval training (HIIT) had a positive effect in developing the special endurance، which was reflected in developing the performance of the players in the research sample، and the researchers recommend using High-intensity interval training (HIIT) method in developing physical abilities and offensive skills of female handball players.